Pre-service Teachers Perspectives towards English Teaching as a Career Option - Mela Tustiawati, Ida Ayu (Udayana Journal of Social Sciences and Humanities; Vol 3 No 2 (2019): UJoSSH, September 2019, 2019)
Education is one of the parameters to the success of a country. As part of the education system, teachers play an important role. The teaching profession that is now considered to be a well-respected profession in society used to be considered as a way to show your dedication to the country. With the change of view towards the teaching profession, more people are attracted to this profession. However, the number of students who enroll themselves in the teaching training universities and the numbers of graduates who become teachers are not the same. Some of them may become teachers but some of them decide to choose a different career path. This study tries to identify the initial perspectives of the pre-service teachers on the English teaching as a career option through the application of questionnaires. The result shows that majority of the participants have positive perspectives towards English teaching as a career option. They view English teaching as a career that will give them a chance to work with the younger generation and help others. It is also viewed as a respectable job that is quite flexible in their application. Even though the current teaching profession offers good financial support, the finding shows that it is not the main reason why the participants decide to be a teacher.